PENGARUH KEMAMPUAN KERJA, FASILITAS KERJA DAN PRINSIP PROSEDUR KERJA TERHADAP KINERJA KARYAWAN RUMAH SAKIT SURYA INSANI PASIR PENGARAIAN - Yusi Hasmita; Makmur (Program Studi Manajemen Universitas Pasir Pengaraian, 2020)
This study aims to determine the effect of work ability, work facilities and working principle principles affect the performance of employees of Surya Insani Pasir Pengaraian Hospital, both partially and simultaneously. The study population was all employees at Surya Insani Pasir Hospital. The sampling technique uses a purposive sampling technique with 59 respondents. Data collection methods using observation, questionnaires, interviews and documentation. The instrument reliability test includes the validity test and the reliability test, Data analysis using multiple linear regression analysis using the SPSS program. Partially, it was obtained t-work capability of 0.131, work facilities of 5.557 and principle of work procedures of 10.200. Simultaneously, an F-count of 36,074 was obtained. The results showed that 66.3% of employee performance was influenced by work ability, work facilities and working procedure principles, while the remaining 33.7 were influenced by other variables not examined in this study. The conclusion of this study is based on the partial test results only variable work facilities and principles of work procedures that significantly influence employee performance, while simultaneously work ability, work facilities and work procedure principles have a significant effect on employee performance.